Short-tailed bats (Carollia: Phyllostomidae) from Gorgona National Natural Park (Colombia) and its biogeographical implications - Murillo-García, Oscar E. (2014)
Taxonomy of short-tailed bats (Phyllostomidae: Carollia) has been unclear due to the extreme morphological similarity among species and the significant morphological variation within species. The identity of theCarollia species in Gorgona National Natural Park (Colombian Pacific) has been controversial due to the high morphological similarity between Carollia perspicillata and C. brevicauda. C. perspicillata is common in lowlands, and more likely to be the Gorgona species than C. brevicauda, while geological evidence suggests that common between 1 500 and 3 000m. We recorded eight measurements from jaws and skulls of confirmed C. perspicillata (24 individuals) and C. brevicauda (23) and 35 individuals captured in Gorgona. Discriminant analyses showed that, contrary to expectations based on current altitudinal distributions, the Gorgona population is morphologically closer to C. brevicauda. Biological evidence suggests that Gorgona was connected in the past to mainland South America. Gorgona may be the highest part of a now submerged mountain range (“Cordillera de la Costa”) that was part of the continent during the Pleistocene glaciations. Consequently, I hypothesize that C. brevicauda colonized Gorgona overland during last Pleistocene glaciations. Rev. Biol. Trop. 62 (Suppl. 1): 435-445. Epub 2014 February 01.